Organizational Transition and Systematic Governance Labor Relations in Enterprises - Qu, Jingdong (Social Development Experiences in China,, 2018)
By assessing the transition in enterprise-employee relations in China over the six decades since the founding of the nation and the three decades since the implementation of a reform and opening up policy, this book investigates these changes from three key perspectives: occupation, operation and governance. The book chiefly analyzes the unit system structure of enterprises and mechanisms such as apprentice systems inside organizations and proposes a combination of systematic governance and civic governance. Further, it investigates in detail the transition in labor relations in township, state-owned and private enterprises under the contract system, market system and project system, reviews the factors contributing to contradictions in labor relations at different periods, and puts forward options for modifying labor relations in various ways, including their system and structure.